Sustaining a Concept-Based Curriculum: Beyond the Launch. Issue 1 (January 2022) - Solheim, Karen; Mittelstadt, Karen; Muehrer, Rebecca; Pinekenstein, Barbara; Willis, Danny
Abstract : Background: Many schools of nursing are transitioning to a concept-based curriculum (CBC) to better prepare students to practice across complex practice settings. Problem: Current literature focused on transitioning to a CBC lacks discussion on how to sustain a CBC once it is implemented. Approach: In this article, the authors emphasize the importance of intentionally sustaining a dynamic CBC and provide strategies to accomplish this aspect of the curriculum trajectory. Conclusion: The authors recommend a multipronged approach to sustainability that takes into account the dynamic nature of curricular change, implementation, and evaluation. Strategies are centered around themes of promoting effective use of a dynamic curricular model, stakeholder engagement, and leadership.